2005
DOI: 10.1007/s11010-005-8216-1
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the p38 MAP kinase in Cr(VI)-induced growth arrest and apoptosis

Abstract: Hexavalent chromium [Cr(VI)] is a carcinogenic genotoxin commonly found in industry and the environment. DNA damage resulting from Cr(VI) exposure triggers numerous stress responses, including activation of cell cycle checkpoints and initiation of apoptosis. Mechanisms controlling these responses, while extensively studied, have yet to be fully elucidated. Here, we demonstrate that the p38 mitogen-activated protein kinase (MAPK) is activated by Cr(VI) exposure and that inhibition of p38 function using the sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…Of note, a high portion of genes which have been shown to be involved in response to oxidative stress were increased by Cr(VI) treatment and were further reverted by pretreatment of EGCG. For instance, dual specificity phosphatases (DUSPs; DUSP5, DUSP6, DUSP7, and DUSP8 in the present study), a group of enzymes that belong to the superfamily of protein-tyrosine phosphatases, participate in the control of MAPK signaling pathway (Jeffrey et al, 2007) which is highly responsive to ROS (Son et al, 2011a) and has been shown to be involved in Cr(VI)-induced growth arrest and apoptosis (Wakeman et al, 2005). AP-1 family genes FosB and ATF3 are key early responders that demonstrate quantitative up-regulation of expression in response to oxidative stress (Chaum et al, 2009) and their activation is inhibited by a well-known antioxidant ascorbate in retinal pigment epithelium cells (Yin et al, 2010).…”
Section: Discussionmentioning
confidence: 92%
“…Of note, a high portion of genes which have been shown to be involved in response to oxidative stress were increased by Cr(VI) treatment and were further reverted by pretreatment of EGCG. For instance, dual specificity phosphatases (DUSPs; DUSP5, DUSP6, DUSP7, and DUSP8 in the present study), a group of enzymes that belong to the superfamily of protein-tyrosine phosphatases, participate in the control of MAPK signaling pathway (Jeffrey et al, 2007) which is highly responsive to ROS (Son et al, 2011a) and has been shown to be involved in Cr(VI)-induced growth arrest and apoptosis (Wakeman et al, 2005). AP-1 family genes FosB and ATF3 are key early responders that demonstrate quantitative up-regulation of expression in response to oxidative stress (Chaum et al, 2009) and their activation is inhibited by a well-known antioxidant ascorbate in retinal pigment epithelium cells (Yin et al, 2010).…”
Section: Discussionmentioning
confidence: 92%
“…Both metals appear to induce oxidative stress (Valko et al, 2006), activate the mitogen-activated protein kinases p38, JNK and ERK (Chuang and Yang, 2001), and induce inhibition of DNA replication and mitosis (Wakeman et al, 2005). However, while the effects of cadmium on DNA synthesis and mitosis were independent of ATM signaling, chromium activated ATM apparently by inducing DNA dsb in S phase cells (Ha et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant or excessive expression of iNOS leads to an accumulation of nitric oxide, which can participate in cancer development (Weiming et al , 2002; Chen et al , 2005). Cr(VI) exposure also leads to activation of mitogen-activated protein kinases (MAPKs), including c-Jun N-terminal kinase (JNK)1/2, p38, and extracellular-signal regulated kinase (ERK)1/2 (Gao et al , 2002; Wakeman et al , 2005; Chen et al , 2009). …”
Section: Introductionmentioning
confidence: 99%